About pay : discussing compensation - Carey, James F. (Crisp Pub. Menlo ParkUS, 1994)
Provides guidance for supervisors who need to discuss various aspects of remuneration with employees. Eight case study examples of relevant situations are presented with exercises and review commentaries.